Biologia reprodutiva de curicaca(theristicus caudatus) no Sul do Brasil, no domínio da Mata Atlântica - RS - Dal Corno, Renata De Boni (Universidade do Vale do Rio dos Sinos, 2012)
The Curicaca, Theristicus caudatus (Boddaert, 1783) is a species that has a high capacity for adaptation, occurring in different environments, being very common in environments anthropized, nesting even close to residences. Uses a wide range of habitat and therefore can achieve great distribution areas, allowing a greater number of individuals has been established, wich contrasts with the small amount of existing studies with this species. The lack of population data does not allow to determinate the real situation of the species involved in the study, making it difficult the implementation of management practices and effective conservation for the Curicaca. Thus understand the behavior and reproductive biology supports in the comprehension of patterns of natural history and is fundamental to conservation measures. This study aimed to evaluate the behavior and reproductive success of nesting groups of Theristicus caudatus on the upland of Rio Grande do Sul. We conducted behavioral observation and counting of individuals, and were assessed differences in behavior between groups, and evaluate reproductive success. The differences between the behavior and reproductive success rates showed that the environment, especially with regard to availability of food influences the frequency of behaviors and reproductive success.
Keywords: Etologia; Reprodução; Sucesso reprodutivo; Etology; Breeding; Reproductive success; ACCNPQ::Ciências Biológicas::Biologia Geral